Pengaruh Elemen Interior Zangrandi Ice Cream Surabaya terhadap Pengalaman Nostalgia Pengunjung - Fausta Ottoni Sasi; Sriti Mayang Sari; Celline Junica Pradjonggo (Intra, 2019)
Nostalgic experience is one of the ways to attract visitors to choose the desired space. The nostalgia experience itself is the emergence of a "feeling" that has generated through various things around the individuals, as one of the triggers is the presence of interior elements in a space that can be captured by the Sensory inputs aspects consisting of visual, hearing, touch, taste, and smell (Hwang & Hyun, 2013). Marchegiani & Phau (2010) also said that the nostalgia itself was divided into 2 different points of view, ‘The way I was ’ nostalgia that means personal nostalgia, and ‘The Way it Was’ nostalgia that means historical nostalgia. This study shows how interior elements in a space can influence the emergence of nostalgic experiences that surrounds the visitors' emotional perceptions. The object used in this study is Zangrandi Ice Cream on Jl. Yos Sudarso Surabaya, which is one of the cultural heritage of Surabaya that has been established since 1930. This study uses qualitative and quantitative methods. The results from this study concludes that the interior elements of Zangrandi's outer area that has captured by visual sensory inputs became the most powerful trigger in giving nostalgia experiences, because in general, there has not been much change since it was found.